ANALISIS WACANA FEMINISME PROGRAM ACARA SANTAI SIANG EDISI KAMIS KEUANGAN DI WOMAN RADIO JAKARTA - Widarti Widarti (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
The existence of radio segmented by women makes new hope for women's public space to form a positive image for women. Through the Santai Siang di Woman Radio program the formation of a positive image of women was developed in the presence of various different topics that were presented to support women's independence in the process of forming a positive image of women in the community. Researching the Sanatai Siang Thursday Financial Edition program program by discussing regulating family finances. Using feminist discourse analysis in the Santai Siang program. The research approach is a qualitative descriptive method developed by Sara Mills, which is also often called critical discourse analysis with a 'feminist' perspective. The results showed that Woman Radio in the Santai Siang program tried to position women into a positive image, women emerged as not inferior to men, but in the domestic sector women still carried out their responsibilities to carry out their roles as working mothers, housewives and wife. Keywords: Feminist Discourse Analysis, Relaxing Day Program, Woman Radio